2015
DOI: 10.1007/978-3-319-19665-7_10
|View full text |Cite
|
Sign up to set email alerts
|

Coloring Channel Representations for Visual Tracking

Abstract: Abstract. Visual object tracking is a classical, but still open research problem in computer vision, with many real world applications. The problem is challenging due to several factors, such as illumination variation, occlusions, camera motion and appearance changes. Such problems can be alleviated by constructing robust, discriminative and computationally efficient visual features. Recently, biologically-inspired channel representations [9] have shown to provide promising results in many applications ranging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…However, the CSK tracker only used greyscale features to train the filter, and this largely limited its performance. To overcome this disadvantage, Danelljan et al [21] integrated the image's color properties into the CSK tracker, and experiments showed that this method significantly improved its performance. Then, with the kernelized correlation filter (KCF)/discriminative correlation filter (DCF) tracker [22] designed by Henriques et al, the process of feature extraction was further optimized.…”
Section: Correlation-filter-based Trackersmentioning
confidence: 99%
“…However, the CSK tracker only used greyscale features to train the filter, and this largely limited its performance. To overcome this disadvantage, Danelljan et al [21] integrated the image's color properties into the CSK tracker, and experiments showed that this method significantly improved its performance. Then, with the kernelized correlation filter (KCF)/discriminative correlation filter (DCF) tracker [22] designed by Henriques et al, the process of feature extraction was further optimized.…”
Section: Correlation-filter-based Trackersmentioning
confidence: 99%
“…Thus, the result N d {x d } is a continuous feature map with a period of T to be used for further computation. CFWCR framework negates hand-crafted features such as HOG [18] and CN [19], and adopts CNN features to extract feature maps. Specifically, they use VGG-M [23] network pretrained on ILSVRC [24] dataset to extract multi-resolution continuous feature maps, and employ the first and the fifth convolutional layer as two deep feature channels.…”
Section: Base Frameworkmentioning
confidence: 99%
“…Kernelized correlation filter is proposed to get a multi-channel extension of linear correlation filters [9]. To integrate multi-resolution feature maps, continuous convolution operators for visual tracking are also proposed [4] and utilized by many state-of-the-art trackers, such as ECO [3] and CFWCR [12], among which CFWCR exploits the great power of deep convolutional neural networks (CNN) features without using any hand-crafted features such as HOG [18] or color names [19], and achieves great performance in both accuracy and robustness. Afterwards, there are also trackers focusing on foreground feature selection [14] and reliability learning [20].…”
Section: Introductionmentioning
confidence: 99%
“…Bolme et al [5] firstly introduce correlation filter into visual tracking with grayscale samples, keeping the object scale fixed in tracking . Afterwards, some methods [9,10,11,6,12,13] improve performance with the help of multi-channel features, such as HOG [14] or Color-Names [15]. KCF [6] and MKCF [13] make kernelized extensions of linear correlation filter to further improve the performance.…”
Section: Related Workmentioning
confidence: 99%